Reinterpeting Nietzsche: An Introduction to the Textualists' Approach - Yulius Tandyanto (Jurnal Filsafat "WISDOM", 2023)
The core of Nietzsche's philosophy is typically articulated comprehensively by contentists through key concepts such as the will to power, the eternal return, and the overman. Unfortunately, such goals are frequently arbitrary and lack rigorous textual support. Textists, on the other hand, tend to prioritize a historical-contextual approach in interpreting Nietzsche's texts in order to overcome this weakness. The textists' approach is distinguished by the genetic and literary analysis of the critical editions of Nietzsche's texts compiled by Colli/Montinari. As a result, this article begins with a brief topography of the critical editions, focusing on the role of KGW IX in genetic analysis. Furthermore, the style of genetic and literary analysis applied to aphorism 36 of BGE becomes a case study to demonstrate how the interpretation differs from that of the contentists. Textists show Nietzsche's creativity as the author of the aphorism that makes parody, irony, and satire of will-causality and moral demands in scientific explanations, whereas contentists interpret the will to power hypothesis as the essence of reality. For textists, the principle of the will to power in BGE 36 is framed in suppositional language, implying that the proposition of the will to power is also unreal.